Public Deliberation on South Korean Nuclear Power Plants: How Can Lay Knowledge Resist against Expertise?. Issue 3 (1st September 2020) - Kim, Sung Hwan; Kim, Hyomin; Song, Sungsoo
Abstract: Through a public engagement exercise held in 2017, 471 Korean citizens decided to resume construction of two nuclear reactors. This article examines the white paper, academic articles, and interview accounts to discuss how distinct groups in their contexts articulated "lay knowledge" as the basis of participatory science and technology governance enacted in Korea. Reflecting on both Brian Wynne's emphasis on public meanings and the STS literatures' attention to lay actors' knowledge-ability, the article reveals the articulation of "lay knowledge" as a process of simultaneously empowering and disempowering the lay public.